Provincial Comparison of Development Status in Nepal: An Analysis of Human Development Trend for 1996 to 2026 - Dhungel, Sanjib (Journal of Management and Development Studies, 2018)
The present study examines the status of Human Development Index (HDI) for 1996, 2001, 2006 and 2011 for seven provinces of Nepal and projected for 2016, 2021, 2026. Base data are obtained from Nepal Human Development Reports (HDR)1998, 2004, 2009 and 2014. The HDI value for the Province 1, 3, 4 and 5 are relatively higher than national average and that for Province 6 is least followed by Province 2 and Province 7. The largest HDI value for 1996 is 0.499 for Province 1, in 2001 is 0.508 for Province 4, in2006 is 0.558 for Province 3 and in 2011is 0.560 for Province. The estimated value for 2016 is 0.578 for Province 1, 0.60 in 2021. Province 1 will continue to lead with 0.622 in 2026. Meanwhile Province 5 will join the club in 2021. Similarly, the lowest HDI value for 1996 is 0.364 for Province 6 and it is lowest for Province 7, in 2001 with value of 0.364. HDI is 0.44 for Province 6, in 2006, and same province is at the lowest rank with value of 0.463 in 2011. Estimated lowest HDI value for 2016 is 0.486 for Province 6, and it will be 0.509 in 2021, and it will be 0.531 in 2026 for this Province. There is smooth growth on HDI over time i.e. impact of investment for development have positive result in Province 3, Province 4 and Province 6, followed by Province 1 and Province 7. Inconsistent growth is observed in Province 5 and Province 2.